Adherence to Secondary Prevention and Influential Factors in Individuals with Coronary Angioplasty - Henao López, Vanesa; Triviño Vargas, Zaider (Investigación y Educación en Enfermería, 2020)
Objective. To explore the relation between adherence to secondary prevention and factors that influence on said adherence in people with acute coronary syndrome, who underwent percutaneous coronary angioplasty in a clinic in Medellín. Methods. Cross-sectional study on a random sample of 128 volunteer patients. A questionnaire was used for sociodemographic variables, the “Scale to measure therapeutic adherence for patients with chronic diseases, based on explicit behaviors” by Trujano, Vega, and Nava and the “Instrument to evaluate adherence by patients according to influential cardiovascular risk factors” validated by Consuelo Ortiz. Results. Socioeconomic factors influenced in very low manner on the adherence to secondary prevention; factors related with the therapy did so moderately and patient factors influenced in low manner. No relation was found between the health provider factor and said adherence. Conclusion. Factors exist that influence in a lesser or higher measure on adherence to secondary prevention and which must be recognized in people with coronary angioplasty to designstrategies to improve this aspect of self-care.